2014
DOI: 10.1159/000368226
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Trauma Leads to a Shorter Survival in a Murine Orthotopic Pancreatic Cancer Model

Abstract: Background: Abdominal surgery is frequently followed by immune dysfunction usually lasting for several days. This is especially important in cases with tumour diseases as an intact immune function is essential in this situation. Therefore, we analysed the outcome of tumour-bearing mice in a mouse model of surgically induced immune dysfunction (SID). Methods: In male C57BL/6 mice, a pancreatic tumour was implanted orthotopically. Following tumour implantation, the model of SID was applied. The control groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
1
1
Order By: Relevance
“…In the present study, SII had no impact on the overall survival. This is in contrast to the results reported by Menges et al [ 24 ]. In this study, tumour-bearing animals subjected to SID showed a significantly reduced survival compared to the non-operated control mice, while tumour growth was similar in both experimental groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, SII had no impact on the overall survival. This is in contrast to the results reported by Menges et al [ 24 ]. In this study, tumour-bearing animals subjected to SID showed a significantly reduced survival compared to the non-operated control mice, while tumour growth was similar in both experimental groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with previous studies, we observed no influence of SID on the tumour growth as analysed by MRI scan on day 8 and day 27 following the tumour implantation [ 24 ]. The increase in tumour volume is only one aspect of the disease progress, while the interaction of immune response and tumour progress is most complex.…”
Section: Discussionsupporting
confidence: 93%
“…MRI plays an important role in the molecular and functional imaging of cancer [12]. Our group has published interesting results for noninvasive monitoring of tumor growth in a murine model for pancreatic cancer [13] and for tumor growth of pancreatic cancer following surgical trauma [14]. In inflammatory situations MRI can generate morphologic information at the site of infection by providing three-dimensional spatially resolved information.…”
Section: Discussionmentioning
confidence: 99%